Chapter Resistenze e storie di rom e sinti per costruire insieme la memoria collettiva - Rizzin, Eva (Public History of Education. Teorie, esperienze, strumenti, 2022)
The contribution aims at discussing the word "Resistenza" in the framework of the life of the communities sinti and rom, between present and past decades. On one side the paper aims at highlighting the contribution rom and sinti gave to Resistance and ti-fascist movement, on the other side it shows sinti and rom's resistance against prejudices and stereotypes which determine their present. The riappropriation of their communitarian history as their national history can be considered as a powerful tool for building people's identity as citizens and it marks a path toward sharing and inclusion.